The need for ICT- induced Organizational Transformation among the Public Sector Banks in Sri Lanka. - Selvarajan, P. (Global Science and Technology Forum, Singapore., 2010)
This paper focuses the need for the organizational transformation in the public sector banks in Sri Lanka. Bank of Ceylon and People’s bank are the two major public commercial banks in Sri Lanka. The author investigated the need for the ICT induced organizational transformation in these banks as a case study. Further the five levels of ICT induced Organizational Transformation process identified by Venkatraman (1990) has been compared with the Sri Lankan public sector banks and recommended possible ICT strategies to be implemented in future in order to reduce the customer traffic and sustain in the competitive market.
Keywords: Information and communication technology; Organizational transformation; Business process redesign; Business network redesign; Business scope redefinition